Gambaran Realisasi Belanja Dana BOK Puskesmas Air Putih Kota Samarinda: Tinjauan Efektivitas dan Pemanfaatan Anggaran-- (Analysis of the Health Operational Assistance (BOK) Fund Realization at Puskesmas Air Putih, Samarinda : An Evaluation of Effectivene - Zheditya Ayu Syawalia; Ratno Adrianto; Akhmad Azmiardi (Mulawarman International Conference on Tropical Public Health, 2025)
Background :Health is a fundamental right guaranteed by the 1945 Constitution of the Republic of Indonesia and has become a national development priority under the 2020–2024 (RPJMN). One of the government’s key health financing policies to strengthen primary health services is the Health Operational Assistance Fund (BOK) Objective :To provide a quantitative overview of the expenditure realization of the BOK Fund at Puskesmas Air Putih Samarinda in 2024 and to evaluate the effectiveness and utilization of the budget based on the principles of effectiveness, efficiency, transparency, and accountability as stipulated in the Ministry of Health Regulation No. 18/2024. The study employed a descriptive method with secondary data analysis sourced from BOK financial realization reports for 2022–2024 Research Methods/ Implementation Methods :The study employed a descriptive method with secondary data analysis sourced from BOK financial realization reports for 2022–2024 Results :The findings show the average realization rate of the BOK budget over the past three years reached 88.9%, with a decline in 2024 to 82%, despite a significant increase in the total allocation. The pattern of fund absorption was uneven, with most expenditures occurring in the fourth quarter. Analysis based on George R. Terry’s (1972) POAC theory (Planning, Organizing, Actuating, Controlling) identified issues in data-based planning, suboptimal intersectoral organization, inconsistent implementation, and reactive supervision Conclusion :The effectiveness of BOK management is influenced by misalignment among managerial functions; therefore, strengthening performance-based planning and monitoring is required to support the transformation of primary health services at the Puskesmas